Online-Customers Segmentation on PT. Rumah Mebel Nusantara (Ikea) in Semarang Region By Using K-Means Analysis With SPSS - Finnia Ayu Kirana, Astried; Esvandiary Iswari, Neisya; Mafatir Romadhon, Damar; Heikal, Jerry (Syntax Corporation, 2023)
Business is an activity carried out by individuals and organizations that create value through goods and services to obtain a profit. In running a business, marketing strategy is the main key in product development for the progress of the company. Marketing is not only for product and service development, but also needs to take into account customer segmentation. Segmentation has done using K-Means Clustering based on SPSS. In this study, researchers took a case study at PT. Rumah Mebel Nusantara (IKEA) in the Semarang area by conducting research on 306 respondents to IKEA online customers. In this study obtained 3 clusters. Where cluster 1 is a Methodical Customer, Cluster 2 is referred to as a Humanistic Customer, and Cluster 3 is referred to as a Spontaneous Customer. Based on the results of data processing using SPSS, researchers chose Cluster 3 because this cluster has a high potential to increase sales with the type of purchase and the number of transactions are greater than the other 2 clusters. This cluster will tend to be more loyal than the other 2 clusters because this type of customer if they satisfied with the brand they will buy it.